Efficacy of Cryoballoon Pulmonary Vein Isolation in Patients With Persistent Atrial Fibrillation. (9th March 2016) - GUHL, EMILY N.; SIDDOWAY, DONALD; ADELSTEIN, EVAN; VOIGT, ANDREW; SABA, SAMIR; JAIN, SANDEEP K.
Cryoballoon Ablation for Persistent Atrial Fibrillation: Introduction: Cryoballoon PVI has emerged as an alternative to radiofrequency PVI for the treatment of paroxysmal AF. The optimal strategy for patients with persistent AF is unclear as data are limited. Methods: We analyzed a prospective registry of consecutive patients with persistent AF who underwent Cryoballoon PVI at a single center between 2011 and 2014. Patients were assessed for atrial arrhythmia recurrence after a 3‐month blanking period at 6 months, 1 year, and 2 years postprocedure. Recurrence was based on typical symptoms, ECG, or event monitor evidence of AF. Kaplan–Meier analysis was used to estimate arrhythmia‐free survival. Results: Final analysis included 69 patients who underwent Cryoballoon PVI with a mean age 59.4 ± 8.1 years, 85.5% male, 53.6% HTN patients, CHA2DS2‐VASC score 1.6 ± 1.2, and LA size 4.5 ± 0.6 cm. The single procedure atrial arrhythmia recurrence‐free rate at 1‐year postprocedure after a 3‐month blanking period was 59% and 50% at a mean follow‐up of 607 days. Of the recurrence‐free group, 17% were taking previously ineffective antiarrhythmic medications. In comparing patients with persistent AF duration <1 year versus >1 year, there was a trend toward greater AF recurrence‐free rates in the <1 year group (66% vs. 55%, P = 0.09). Conclusion: Cryoballoon PVI appears to be an effective initial strategy in treating persistent AF, with an AF recurrence‐free rate of 59% at 1 year.